A spice, not a topping: Social inclusion and gender integration in the TAFSSA portfolio - Kumar, Neha; Quisumbing, Agnes R. (International Food Policy Research Institute, 2023)
Anyone familiar with South Asian cuisine knows that the key to its flavor are the spices – the masala, either whole or ground — often tempered in oil or clarified butter at the start of the cooking process. Similarly, well-designed gender research treats gender as an ingredient essential to the dish itself, not a topping or afterthought. But what does one do if a research program has begun, with uneven attention to gender issues? How can attention to gender be introduced at different stages and different parts of a research portfolio, where it makes the most sense? Just as different recipes call for different spices to create unique flavors, likewise, different research projects benefit from different degrees of focus on gender. In some contexts, gender may not be the key driver of inequality in diet, health, and nutrition outcomes, though it may intersect with other factors that contribute to marginalization, notably caste, class, and lifecycle stage. Thus, a research portfolio must have a coherent and strategic approach to integrating gender and social inclusion.